The dubious disciples doubt and disbelief in the post-resurrection scenes of the four gospels - Woodington, J. David (Berlin Boston De Gruyter, 2020)
Frontmatter -- Contents -- Acknowledgments -- 1 Introduction -- 2 The Gospel Of Mark -- 3 The Gospel Of Matthew -- 4 The Gospel Of Luke -- 5 The Gospel Of John -- Conclusion -- Appendix: The Disciples In Ancient Christianity -- Bibliography -- Index
The accounts of Jesus's resurrection in the Gospels are among the most widely discussed passages in the New Testament, and a classic element of the resurrection story is the doubt felt by the disciples when they encountered the risen Lord. In spite of this, scholars have paid relatively little attention to the striking divergences in the portrayal of the disciples across the four Gospels. The Longer Ending of Mark has them stubbornly refuse to believe multiple reports of the resurrection before being upbraided by Christ, Matthew tersely notes their doubts in a single verse and never resolves the problem, Luke depicts a group who are simultaneously terrified and joyful, and John describes the eponymous Doubting Thomas and his request to touch the risen Lord for himself. The Dubious Disciples uses narrative criticism to examine the ways in which each Gospel characterizes the disciples post-resurrection and how these authorial choices influence readers' evaluations of both the disciples' doubts and the doubts they may feel in their own lives. The lessons learned about the nature of doubt vary considerably from one Gospel to the next, and this monograph is the first devoted to a comparison of doubt across all four Gospels
The Dubious Disciples provides a literary examination of the four scenes of the disciples doubting the appearance of the resurrected Jesus in the canonical Gospels. Each Gospel offers a unique account of this episode, and the differences between them dramatically affect how readers evaluate the disciples' actions and perceive the role of doubt in the Christian experience
Mode of access: Internet via World Wide Web.
In English
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Apostles; Belief and doubt; Jesus Christ-Appearances; Jesus Christ-Resurrection; Bible.-Gospels-Criticism, interpretation, etc; RELIGION / Biblical Criticism & Interpretation / New Testament; RELIGION / Biblical Studies / Jesus, the Gospels & Acts; RELIGION / Biblical Studies / New Testament; Resurrection; Discipleship; Doubt; Gospels; Hochschulschrift